The Influence of Islamic Spiritual Extracurricular Activities on PAI Learning Outcomes of Students at State Senior High School 1 Bojonggede, Bogor Regency - Eva Siti Faridah; Salma Aisyah Amini (Bulletin of Islamic Research, 2023)
Abstract Islamic Spiritual Activities (ROHIS) are highly beneficial in shaping a generation of Muslims who not only impact learning outcomes but also influence their spirituality. This research aims to address the issue of whether ROHIS activities affect the learning outcomes of Islamic Religious Education (PAI). This study uses a Quantitative Method, also known as field research, conducted at SMA Negeri 1 Bojonggede, Bogor Regency. It provides an overview of the issues through analysis with a scientific approach based on the situation in the field. The study aims to examine how the influence of Islamic Spiritual Extracurricular Activities affects the learning outcomes of PAI for 11th-grade students at SMA Negeri 1 Bojonggede. The research data collected were analyzed using SPSS through several tests, including Descriptive Data, Instrument Test, Prerequisite Test, and Hypothesis Test. Based on the descriptive data calculations using descriptive statistics, it was found that the average score for variable X = 45.31 and variable Y = 85.09, the median or middle value for variable X = 45.00 and variable Y = 85.00, the mode or most frequent value for variable X = 40 and variable Y = 88, the standard deviation or difference score for variable X = 10.225 and variable Y = 2.291, the variance for variable X = 104.544 and variable Y = 5.249, the range score for variable X = 56 and variable Y = 6, the minimum score for variable X = 22 and variable Y = 82, the maximum score for variable X = 78 and variable Y = 88, and the total score for variable X = 1450 and variable Y = 2723. To determine whether there is an effect of variable X on Y, a Hypothesis Test was conducted using the Pearson product-moment correlation formula, a Significance Test using the t-test, and a Determination Coefficient. The results of the correlation test showed that the value of rhitung = 0.442 > r table = 0.266, Ha is accepted and Ho is rejected, indicating a positive influence of ROHIS activities on PAI learning outcomes. The results of the significance test show that the p-value (sig.) = 0.011 > 0.05 and the t-count value = 2.700 > t-table = 1.674, so Ha is accepted and Ho is rejected, indicating a significant correlation between ROHIS activities and PAI learning outcomes. The contribution calculation (R Square/Determination Coefficient) or the influence of ROHIS activities on PAI learning outcomes is R2 x 100% = 0.4422 x 100% = 19.5%. This means that the contribution of ROHIS activities affects PAI learning outcomes by 19.5%, while 80.5% is influenced by other factors. These factors may include external and internal factors.